2019
DOI: 10.1177/1099800419869845
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcranial Direct Current Stimulation on Inflammation in Older Adults With Knee Osteoarthritis: A Bayesian Residual Change Analysis

Abstract: Transcranial direct current stimulation (tDCS) has demonstrated effectiveness in reducing clinical and experimental measures of pain in patients with chronic pain; however, research examining the mechanisms of action for the effects of tDCS has been lacking. The present study investigated the effect of active tDCS on measures of inflammation and stress. Older adults (aged 50–70 years) with knee osteoarthritis (OA) were randomly assigned to receive daily 20-min sessions of either tDCS ( n = 20) or sham tDCS ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…Age is the strongest factor associated with OA development, thus with global aging process, the burden of KOA to the health care systems worldwide is expected to increase [ 5 , 6 ]. Besides the pain, older individuals with KOA may have a poor quality of life due to stiffness, deformity, limitation in range of motion, dependence to perform activities of daily life; consequently leading to increases in economic and social costs globally [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age is the strongest factor associated with OA development, thus with global aging process, the burden of KOA to the health care systems worldwide is expected to increase [ 5 , 6 ]. Besides the pain, older individuals with KOA may have a poor quality of life due to stiffness, deformity, limitation in range of motion, dependence to perform activities of daily life; consequently leading to increases in economic and social costs globally [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same period, Khedr et al 27 More recently, Suchting et al 28 conducted a randomized, double-blind, placebo-controlled clinical trial with data obtained from 40 patients with knee osteoarthritis treated with tDCS (2 mA/35 cm2, 20 min) on 5 consecutive days applied to the M1 region contralateral to the affected knee. The following stress and inflammation markers were measured: IL-6, IL-10, TNF-α, PCR, cortisol and BE.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, our group is currently investigating the efficacy of tDCS as a therapeutic, nonpharmacological approach to chronic knee pain in a series of randomized clinical trials, and pilots studies conducted thus far have shown a significant reduction of pain perception associated with neuromodulation. 30,31,[31][32][33][34] A large-scale demonstration of the effects of tDCS on clinical pain through a clinical trial has yet to be completed, hence the goals of this pilot study of relating fNIRS-derived cortical hemodynamics to longitudinal tDCS and to self-reported pain measures (regardless whether the pain is altered by tDCS alone or in addition to other factors) can be considered independent from each other. Also of relevance, prior research had used fNIRS to measure the cortical hemodynamic response to thermal pain, 39,46,47,55 but our pilot study appears to be the first where fNIRS data in response to thermal stimulation has been acquired concurrently with a tDCS treatment longitudinally for two weeks (three longitudinal sessions: one observation before treatment and two observations during the treatment).…”
Section: Discussionmentioning
confidence: 99%
“…23 This M1-SO electrode montage purportedly increases the excitability of afferent or efferent neuronal structures involved in pain processing and increases pain inhibitory controls on the motor, somatosensory, and frontal cortices implicated in pain sensitivity. [24][25][26][27][28][29] Our group [30][31][32][33][34] as well as others 24,25,[27][28][29]35 have shown that a 2-mA current, M1-SO tDCS treatment applied in the clinic effectively improves chronic pain function in a variety of populations, including knee OA. In addition, of relevance to this study, the portability, connectivity, and relative ease-of-use of modern tDCS devices make this neuromodulation technique suitable for an in-home, selfadministered regimen that avoids patients' daily visits to a clinical site.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation